Influência da gestão de casos em um programa de prevenção de quedas para idosos nas variáveis funcionais: estudo clínico randomizado - Alberto, Silsam Napolitano (2022)
Advances in technological, economic and health conditions have increased the life expectancy of human beings. Currently, the number of older adults is approximately 1 billion worldwide according to the World Health Organization. One of the major concerns of the older population is the falls risk. In Brazil, the prevalence of falls in 2017 ranged from 10% to 35% in older people living in urban areas. Falls generate high expenses for public and private health systems; have harmful consequences for the physical and mental health of the older adults, such as fractures, injuries, injuries, psychological consequences, such as fear of falling again, loss of confidence and social isolation, in addition to institutionalization, increase in emergency room visits and long-term hospitalizations. Case management seeks to identify the problems and conditions that can change for the older adults individually in order to meet the needs found, this model of care associated with the health care plan is able to offer physical, psychological and social assistance that goes beyond the traditional models of health care. Therefore, this dissertation aimed to evaluate the influence of case management applied to a fall prevention program in order to reduce the risk of new episodes of falls in the older adults. The dissertation was divided into two studies. Study 1 “A Case Management Program at Home to Reduce Fall Risk in Older Fallers: a Single-Blind Randomized Controlled Trial Protocol (Magic Study)”. Objectives: to describe the protocol used in a single-center, parallel-group (Intervention Group and Control Group) and single-blind (evaluators) randomized clinical trial involving a case management-based fall prevention program for older adults who had suffered 2 or more falls in the last 12 years. months. Methods: Community-dwelling older adults will be volunteers and will perform an initial assessment by video call and will be randomly allocated into one of 2 groups: intervention group or control group, volunteers from the intervention group will be invited to participate in the 16-week intervention with physical activity and management risk factors for falls at home by telephone and video calls, the volunteers in the control group will maintain their usual routine, after 16 weeks all will be reassessed by video call. Results: To date, 52 older adults have been recruited for the study. Study 2 “Influence of case management in a fall prevention program for the older people on functional variables: Randomized Clinical Study”. Objectives: To assess the effects of a case management-based fall prevention program on postural balance, functional capacity, presence and sites of pain, falls risk, and risk for osteoporotic fractures over the next 10 years in community-dwelling older adults who suffered 2 or more falls in the last 12 months. Methods: Sixty-two community-dwelling older adults volunteers underwent an initial assessment by video call, after which they were randomly allocated to one of 2 groups: intervention group or control group, volunteers from the intervention group were invited to participate in the 16-week intervention with physical activity and management of risk factors for falls at home by telephone and video calls, the volunteers in the control group maintained their usual routine, after 16 weeks all were reassessed by video call. The evaluators were blinded to the randomization and allocation of volunteers in the groups. Results: There were significant differences after the intervention in the improvement of functional capacity and balance evaluated by the Up and Go Test in the Control group. There were no other significant differences in balance, functional capacity and lower limb strength and in the presence of pain among the volunteers. Conclusion: The association of case management in a program for the prevention of falls in older adults fallers in the community did not present significant results in the functional variables, but it was important for the characterization of pain and fracture probability for the next 10 years in this population.